Pengaruh tiga jenis formula teknologi Sucrosin terhadap pertumbuhan dan produktivitas tebu (Saccharum officinarum L.) - Muhammad Abdul Aziz; Ciptadi Ahmad Yusup; Siswanto Siswanto; Djoko Santoso; Priyono Priyono; Happy Widiastuti (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
Sucrosin technology, have been tested in ​​more than 10,000 ha of sugarcane planting area, resulted in highly variable increases in productivity. However, fulfilling standard operational procedures when implemented on a wide scale is complicated, so it needs to be simplified regarding product formulation and application techniques. This study aimed to evaluate the three different formulas of Sucrosin technology in increasing sugarcane growth and productivity. The study was conducted on PC sugarcane at RNI Plantation, Majalengka, West Java, using the Bululawang 1303 variety. The research design was a completely randomized design with four treatments consisting of Sucrosin technology existing (Se), formula 1 (S1), and formula 2 (S2) and control. The application of formula 2 Sucrosin technology (S2) could significantly increase the height and diameter of sugarcane stalks at 6 and 9 MAP. Sugarcane production in Se, S1, and S2 treatments increased by 22.49% (112.71 ton ha-1), 20.47% (110.85 ton ha-1), and 16.45% (107.15 ton ha-1) compared to controls (92.02 ton ha-1), respectively. These results show that Sucrosin Se technology produces the highest production. Nevertheless, from a technical perspective for implementation in the field, the most straightforward Sucrosin technology is S2. However, further research needs to be conducted in the broader area across different agro-ecologies to confirm the current findings.